Kuliner Lokal Bali sebagai Daya Tarik Wisata: Pengembangan di Candi Tebing Tegallinggah, Gianyar Bali - Yesarela Pandu Mau; I Wayan Rediyasa; Maria Lydia Da Silva (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This study aims to identify the potential of local Balinese cuisine as a tourist attraction at Tebing Tegallinggah Temple, Gianyar, Bali. This temple is a historical site that has great potential to be developed as a cultural-based tourism destination, but currently the use of local cuisine as a tourism element is still not optimal. The method used in this study is a qualitative approach with a descriptive method, through in-depth interviews, observations, and documentation with various parties, including visitors, local culinary business actors, and tourism stakeholders. The results of the study show that tourists have a high interest in traditional Balinese cuisine, but there are limitations in terms of facilities, promotion, and coordination between related parties. With the right strategy, such as improving infrastructure, training for business actors, and effective promotion, local cuisine can be integrated more deeply into the tourism experience at Tebing Tegallinggah Temple. This study concludes that the development of local cuisine will not only increase tourist attractions, but also support the preservation of culture and the economic welfare of the local community.